PDB PENGUATAN PEREKONOMIAN MASYARAKAT DESA SAMBIBULU MELALUI WISATA EDUKASI BERBASIS KEARIFAN LOKAL - Marwiyah, Siti; Hartati, Fadjar Kurnia; Tampubolon, Liosten Rianna Roosida Ully; Luayyi, Sri; Suryawati, Cicilia Tantri (Jurnal Likhitaprajna, 2024)
The Assisted Village Empowerment Program (AVEP) in strengthening the community's economy is very important to improve community welfare and empowerment through the local potential that exists around the Assisted Village. Sambibulu Village, Taman District, Sidoarjo Regency, East Java has a variety of regional potential that needs to be developed, such as water ecotourism, MSME stalls, agricultural equipment rental, agribusiness, and the Sambi Horti Red Guava Farmers Group. The aim of this AVEP program is to increase the level of empowerment of target partners in each partner based on increasing product quality, capacity and competitiveness. The methods used are socialization, training, application of technology, mentoring and evaluation, as well as a desire program. The results of this activity showed an increase in production output by 50% and product quality increased by 65%, diversification of crystal seed guava and shallot planting with an increase in profits of 40%.